The error analysis of narrow-band receiving frequency-modulated signals - S. I. Ziatdinov (Известия высших учебных заведений России: Радиоэлектроника)
It's showed that limitation of the stripe passing in the time of the reception the frequency-modulation signal leads to bad changes of amplitude and frequency in the exiting signal, value of which is depended from meaning of the angle modulation.